A Functional Antagonistic Relationship between Auxin and Mitochondrial Retrograde Signaling Regulates Alternative Oxidase1a Expression in Arabidopsis . Issue 3 (12th May 2014) - Ivanova, Aneta; Law, Simon R.; Narsai, Reena; Duncan, Owen; Lee, Jae-Hoon; Zhang, Botao; Van Aken, Olivier; Radomiljac, Jordan D.; van der Merwe, Margaretha; Yi, KeKe; Whelan, James
Abstract : The induction of mitochondrial stress response is antagonized by auxin signaling revealing regulation of mitochondrial respiratory pathway gene expression by auxin . Abstract: The perception and integration of stress stimuli with that of mitochondrion function are important during periods of perturbed cellular homeostasis. In a continuous effort to delineate these mitochondrial/stress-interacting networks, forward genetic screens using the mitochondrial stress response marker alternative oxidase 1a ( AOX1a ) provide a useful molecular tool to identify and characterize regulators of mitochondrial stress signaling (referred to as regulators of alternative oxidase 1a [RAO s] components). In this study, we reveal that mutations in genes coding for proteins associated with auxin transport and distribution resulted in a greater induction of AOX1a in terms of magnitude and longevity. Three independent mutants for polarized auxin transport, rao3 / big, rao4/pin-formed1, and rao5/multidrug-resistance1/abcb19, as well as the Myb transcription factor rao6/asymmetric leaves1 (that displays altered auxin patterns) were identified and resulted in an acute sensitivity toward mitochondrial dysfunction. Induction of the AOX1a reporter system could be inhibited by the application of auxin analogs or reciprocally potentiated by blocking auxin transport. Promoter activation studies with AOX1a :: GUS and DR5 :: GUS lines further confirmed a clear antagonistic relationship between the spatial distribution of mitochondrial stress and auxin response kinetics, respectively. Genome-wide transcriptome analyses revealed that mitochondrial stress stimuli, such as antimycin A, caused a transient suppression of auxin signaling and conversely, that auxin treatment repressed a part of the response to antimycin A treatment, including AOX1a induction. We conclude that mitochondrial stress signaling and auxin signaling are reciprocally regulated, balancing growth and stress response(s).